Japanese racial identities within US-Japan relations, 1853-1919 - Merida, Tarik (Edinburgh : Edinburgh University Press, 2023)
Considers: Did race really matter? Racial ideology and political pragmatism in U.S.-Japan relations.
"This book retraces the process through which, at the turn of the twentieth century, the Japanese went from a racial anomaly to honorary members of the White race. It explores the interpretation of the Japanese race by Western powers, particularly the United States, during Japan's ascension as a great power between 1853 and 1919. Forced to cope with this new element in the Far East, Western nations such as the U.S. had to device a negotiation zone in which they could accommodate the Japanese and negotiate their racial identity. In this book, Tarik Merida, presents a new tool to study this process of negotiation: the Racial Middle Ground."--
Acknowledgements -- Introduction: The Japanese Racial Anomaly -- On the (ir)relevance of studying race -- Subject and scope -- Theoretical framework--the racial middle ground -- Focus and sources -- Structure of the book -- Part I: Race in the Japanese Context: Early Modern Patterns of Differentiation and the Introduction of Race in Modern Japan -- 1 Patterns of Differentiation in Early Modern Japan -- On the existence of race in early modern Japan -- Confucianism and the 'Middle Kingdom' -- Gender and equality in early modern Japan -- Hairy barbarians: Ainu, foreigners and Japanese civilisation -- 2 The Translation of Race in the Meiji Period -- Introducing modernity: the translation of race in the early Meiji period -- Adapting the concept of race -- Part II: A Racial Middle Ground: Negotiating the Japanese Racial Identity in the Context of White Supremacy -- 3 Between Two Races--The Birth of the Racial Middle Ground between Japan and the West -- Japan and the standard of civilisation: the problem of race against civilisation -- Japan, the West and the racial middle ground -- Racial pessimism and the survival of the fittest -- 4 Two Wars and First Successes: From the Port Arthur Massacre to the Treaty of Portsmouth -- Early benefits of the racial middle ground: the Port Arthur Massacre -- 'Yellow fears' of 'yellow peril': race and the Russo-Japanese War -- Agents of the racial middle ground -- 5 Further Successes and the Limits of the Racial Middle Ground -- The California Crisis -- Becoming visible: Japanese immigration to the United States -- Theodore Roosevelt and the Japanese racial identity -- 6 African Americans and the Racial Middle Ground -- The race at the bottom (I): the Black press and the California Crisis -- The race at the bottom (II): the meaning of African Americans for Japan -- Early Japanese views of African Americans -- The 'Black problem' or how to sell Japanese immigrants -- The human aspect of the racial middle ground -- 7 The End of the Racial Middle Ground -- The crisis goes on: the Alien Land Law of 1913 -- Losing appeal: the West, Japan and alternative visions of world orders -- Embracing yellowness: the appeal of Pan-Asianism -- The collapse of the racial middle ground: the Paris Peace Conference -- Conclusion: The Elusive Japanese Race
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on April 06, 2023).
Tarik Merida is Assistant Professor of Japanese Studies at Freie Universität Berlin. Tarik completed his PhD in 2019 and has published articles in journals including The Asia-Pacific Journal and Japan Review.
eBooks on EBSCOhost
Keywords: Japanese -- Race identity; Race relations -- Political aspects; Japan -- Foreign relations -- 19th century; United States -- Foreign relations -- Japan; Japan -- Foreign relations -- 20th century; Japan -- Foreign relations -- United States; Japon -- Relations extérieures -- 19e siècle.; Japon -- Relations extérieures -- 20e siècle.; Japon -- Relations extérieures -- États-Unis.; POLITICAL SCIENCE / International Relations / General; Diplomatic relations; Race relations -- Political aspects; Japan; United States; 1800-1999